Solitary Bone Cyst Like Areas in Myositis Ossificans: A Breast Mass in a Child. (20th May 2021) - Akatli, Ayse Nur; Uguralp, Sema; Alan, Saadet; Tasci, Aytac; Yildirim, Gokhan
Abstract: Background: Myositis ossificans is an extraosseous, benign tumor-like condition characterized by prominent heterotopic ossification. Cystic degeneration in myositis ossificans is an uncommon entity. Case report: A 13-year-old girl presented with a large and painful breast lump. Physical examination revealed a mobile, hard mass, clinically resembling a fibroadenoma. The mass was excised and diagnosed as myositis ossificans with central bone cyst like changes. Conclusion: Our case represents the first myositis ossificans case with central bone cyst like changes in a child.